Pengaruh Pemberian Buku Saku terhadap Motivasi dan Kepatuhan Ibu Melakukan Senam Hamil - Ni Nengah Arini Murni Murni; I Gusti Ayu Putu Sri Wahyuni Wahyuni; Ni Putu Dian Ayu Anggraeni (Jurnal Bidan Cerdas, 2022)
Introduction: Pregnancy exercise aims to prepare physically and mentally to face and prepare for childbirth. Motivation is still needed to do pregnancy exercise. The choice of method when providing health education is very important to understand the content of the material. Objective: To determine the effect of giving a pocket book on the motivation and compliance of pregnant women doing pregnancy exercise. Methods: Quasi-experimental-group pre and post-test design with control group. The research sample was pregnant women by purposive sampling with each group of 30 respondents. Measurement of motivation and compliance variables before and after the intervention with a questionnaire through the results of observations and monitoring cards. Data were analyzed by univariate and bivariate using Chi square test. Results: In the intervention group, there was a significant difference in maternal motivation (p-value=0.001) and pregnant women's adherence to exercise during pregnancy (p-value=0.042). While in the control group there was no difference in maternal motivation (p-value = 0.214), but there was a significant difference in the compliance of pregnant women in doing pregnancy exercise (p-value=0.000). Conclusion: Provision of pocket books is effective in increasing the motivation and compliance of mothers in doing pregnancy exercise. Future research can design tools that are more practical and effective to monitor compliance and evaluate the effectiveness of pregnancy exercise on the delivery process.